Is it Appropriate for Patients to be Discharged at the Scene by Paramedics? - Tohira, Hideo; Fatovich, D.; Williams, T.; Bremner, A.; Arendts, G.; Rogers, I.; Celenza, A.; Mountain, D.; Cameron, P.; Sprivulis, P.; Ahern, T.; Finn, J. (2016)
BACKGROUND: Outcomes of patients who are discharged at the scene by paramedics are not fully understood. OBJECTIVE: We aimed to describe the risk of re-presentation and/or death in prehospital patients discharged at the scene. METHODS: We conducted a retrospective cohort study using linked ambulance, emergency department (ED), and death data. We compared outcomes in patients who were discharged at the scene by paramedics with those who were transported to ED by paramedics and then discharged from ED between January 1 and December 31, 2013 in metropolitan Perth, Western Australia. Occurrences of subsequent ambulance requests, ED attendance, hospital admission and death were compared between those discharged at the scene and those discharged from ED. RESULTS: There were 47,330 patients during the study period, of whom 19,732 and 27,598 patients were discharged at the scene and from ED, respectively. Compared to those discharged from ED, those discharged at the scene were more likely to subsequently: request an ambulance (6.1% vs. 1.8%, adjusted odds ratio [adj OR] 3.4; 95% confidence interval [CI] 3.0-3.9), attend ED (4.6% vs. 1.4%, adj OR 3.3; 95% CI 2.8-3.8), be admitted to hospital (3.3% vs. 0.8%, adj OR 4.2; 95% CI 3.4-5.1). Those discharged at the scene tended towards an increased likelihood of death (0.2% vs. 0.1%, adj OR 1.8; 95% CI 0.99-3.2) within 24 hours of discharge compared to those discharged from ED. CONCLUSION: Patients attended by paramedics who were discharged at the scene had more subsequent events than those who were transported to and discharged from ED. Further consideration needs to be given to who is suitable to be discharged at the scene by paramedics.